Ready to work english for employment - Shak, Priscilla (Cengage Learning Asia, 2015)
Ready to Work: English for Employment is an indispensable resource book to equip college and university students with vital job seeking skills and oral and written communication skills necessary in the workplace. It provides clear guidelines, complete with various examples of on the job scenarios to expose learners to workplace situations and to help them to attain effective communication skills for future professional use. Additionally, this book provides informative and up-to-date materials relevant to various fields, boosts learner-centered activities, and offers information from key concepts to skills needed in today's business world.